Caribbean SIDS and the Barbados Programme of Action (2008)
Provides an update on the Barbados Programme of Action. Indicates that the Regional Coordinating Mechanism has been set up to play a critical role in helping Caribbean SIDS to achieve their individual and collective targets for their sustainable development.
Keywords: SUSTAINABLE DEVELOPMENT